Pathways to Policy Intervention Aiming at Badhi Community in Karnali Province - Adhikari, Khagendra Prasad (International Journal of Atharva, 2025)
Karnali Province, one of the privileged provinces of Nepal, has particular difficulties when it comes to Badi, the marginalized caste group. This policy mapping offers a badi’s current situation. As a disadvantaged, marginalized, and minority group, the Badi community in Nepal experiences difficulties that are representative of larger problems among underprivileged communities, such as dalits. highlights the possible socioeconomic effects of increased life chances and opportunities in Karnali Province, identifies major obstacles to access and quality, and offers a series of evidence-based policy recommendations. It seeks to explore the existing status of Badhi of Badi people by acting as a catalyst for positive change. While some women have found alternative livelihoods, the fear of their daughters falling into prostitution due to the ongoing socioeconomic marginalization persists. The state’s response must undergo a qualitative change with a genuine commitment to implementing agreements and programs to address structural discrimination and prevent future conflicts as the Badi community continues to advocate for their rights and development efforts for their upliftment. While some women have found alternatives. The research shows the terrible and panicky situation of Badi girls and women due to the multi-layers of exploitation, based on the findings of the research. Although self-respect, access to empowerment, and other rights for the Badi people have been guaranteed by constitutional, legislative, and policy measures, it is yet unclear how effectively these laws have been put into practice. In 2005, the Supreme Court issued a mandamus order, directing the Government to immediately arrange for the citizenship of any children, including the Badi children, who are unaware of their fathers’ whereabouts due to their fatherlessness, in accordance with section 3(2) of the Citizenship Act 2020. In spite of this decree, Badi children have been refused citizenship and birth registration since they do not know who their father is. Since caste-based discrimination, untouchability, and social discrimination against the Badi community and their children are still common, the government and non-governmental organizations should lead effective movements against these forms of discrimination and ensure that the laws against them are applied effectively.